(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Iron concentrations, distribution and migration forms, depending on pH and oxidation – reduction potential, were analyzed in case of the Kemeri-Jaunkemeri occurrence (area about 240 km2) of sulphide containing water (maximal sulphides concentration – 74 mg/l), located in Latvia. Iron content was investigated in 457 wells located within all area of occurrence. Those wells were installed to two aquifers: the Quarternary multi-aquifer and Salaspils aquifer, where occurrence of sulphide containing groundwater is distributed. All groundwater of occurrence is classified in four types depending on oxygen, sulphides and organic matter content in the groundwater. Modeling of groundwater migration forms was carried out, and it is stated that iron migrates basically as Fe2+ in oxygen and suphides non-containing water. Migration forms are influenced by concentration of organic matter in the aquifer. The portion of Fe2+ migrating in a form of free decreases due to formation of complexes with fulvic and humic acids, which can reach 36.5% of all migration forms. Iron migrates as Fe(OH)3 in oxygen containing water (more than 99% of determined forms). Presence of iron is ascertained also in sulphides containing water, where iron migrates basically as (98.8% of determined forms). This occurs due to formation of complexes with sulphydes – FeHS- and Fe(HS)2o.